Investment neutrality in resource rent taxation – revealed preferences of Norwegian oil & gas companies - Julide Ceren Ahi; Atle Blomgren; Atle Guttormsen; Bård Misund; Ragnar Tveterås (Cogent Business & Management)
This study revisits the academic disagreement on the impact of resource rent tax design on oil and gas companies. The disagreement relates to whether the petroleum special tax on the Norwegian Continental Shelf leads to under- or over-investments. Ideally, to ascertain the degree of investment distortion, one would need to conduct an empirical analysis of the private investment decision information of oil and gas companies that is not publicly available. In this study, using a recent major petroleum resource rent tax overhaul as a case study, we adopt an alternative approach and examine information from the industry conveyed by oil and gas companies through the consultation process. If the underinvestment hypothesis is true, then the company should favor a change to a cash flow tax. At the same time, the opposite is true for the hypothesis that the special tax results in overinvestments – companies should be unfavorable towards a tax change. Analyses of oil and gas companies’ responses support the hypothesis that the previous tax regime provided investment disincentives.